2015
DOI: 10.1186/s13071-015-0792-7
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone inhibits brain apoptosis in mice with eosinophilic meningitis caused by Angiostrongylus cantonensis infection

Abstract: Background: Angiostrongylus cantonensis, the rat lungworm, is the major cause of eosinophilic meningitis worldwide. Rats serve as the definitive host of the nematode, but humans can be infected incidentally, leading to eosinophilic meningitis. A previous BALB/c animal study has demonstrated increased apoptotic proteins and decreased anti-apoptotic proteins in mice infected with A. cantonensis. Steroids may be an effective treatment option for eosinophilic meningitis caused by A. cantonensis, but the involved m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…In support of this, Morassutti et al (2013b) and Yong et al (2015a) report no evidence of Wolbachia in their genome sequences. While Foster et al (2008) suggest that the findings of Tsai et al (2007b) may be the result of contamination, it should be noted that not all specimens within a filarial nematode species harbour Wolbachia even if that species is known to possess a Wolbachia endosymbiont (Ferri et al 2011).…”
Section: Nuclear Genomesmentioning
confidence: 99%
“…In support of this, Morassutti et al (2013b) and Yong et al (2015a) report no evidence of Wolbachia in their genome sequences. While Foster et al (2008) suggest that the findings of Tsai et al (2007b) may be the result of contamination, it should be noted that not all specimens within a filarial nematode species harbour Wolbachia even if that species is known to possess a Wolbachia endosymbiont (Ferri et al 2011).…”
Section: Nuclear Genomesmentioning
confidence: 99%
“…In this current study, IL-4, IL-13, IL-19, IL-10, IL-6, IL-27 and IL-5 showed almost no expression in the normal control group, whilst at 14 dpi and 21 dpi, IL-4 and IL-13 significantly increased, followed by IL-19, IL-10, IL-6, IL-27 and IL-5, which were highly expressed. The migration of the worm in the brain of host induced injury and inflammation of CNS [ 42 , 43 ]. Macrophages, eosinophils and lymphocytes gathered at the site of inflammation and Th2-type cytokine secretion such as IL-4, IL-5, IL-10, and IL-13 were increased under the stimulation of worm antigen in the late infection phase.…”
Section: Discussionmentioning
confidence: 99%
“…IL-5, a hemopoietic factor, has been shown to stimulate the proliferation, differentiation, and maturation of eosinophils [29], and an increased CSF IL-5 level and eosinophilia have been reported in eosinophilic meningitis caused by A. cantonensis infection [13,30]. Steroids have been found to induce the apoptosis of eosinophils [31] and inhibit brain apoptosis in mice with eosinophilic meningitis [11]. Taken together, the beneficial effects of steroids on eosinophilic meningitis caused by A. cantonensis infection in this study may have been mediated by improvements in BBB dysfunction, inhibition of the expressions of plasminogen activators and inflammation, down-regulation of 14-3-3 isoform proteins in the CSF, inhibition of mice brain apoptosis, and other unidentified mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…When this parasitic infection occurs in humans and mice (non-permissive hosts), the development of the larvae will stop at the young-adult worm stage in the brain and induce eosinophilia in blood and especially in cerebrospinal fluid (CSF) [813]. Previous studies have shown that transmigration of eosinophils to CSF [13], brain apoptosis [11] and the overexpression of CSF 14-3-3 β [12] are associated with blood brain barrier (BBB) dysfunction in mice and humans infected with A. cantonensis .…”
Section: Introductionmentioning
confidence: 99%